Cronkite's war : his World War II letters home - Cronkite, Walter, IV.; Isserman, Maurice (Washington, D.C. : National Geographic Society, 2013)
A giant in American journalism in the vanguard of "The Greatest Generation" reveals his World War II experiences in this National Geographic book
Foreword by Tom Brokaw -- Map of European Theater -- Cast of characters -- Introduction by Walter Cronkite IV -- A pretty personal matter -- The writing Sixty-Ninth -- The youthful dean of American Air-War writers -- Invasion jitters -- Once this war is over -- Epilogue by Maurice Isserman -- Afterword by Walter Cronkite IV -- Time line.
Includes bibliographical references and index.
Keywords: Cronkite, Walter -- Correspondence; Cronkite, Walter -- Family; Cronkite, Betsy, -- -2005 -- Correspondence; United Press International -- Biography; World War, 1939-1945 -- Journalists -- Correspondence; War correspondents -- United States -- Correspondence; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Campaigns -- Europe; World War, 1939-1945 -- England -- London -- Anecdotes; World War, 1939-1945 -- Personal narratives; Love-letters -- United States